2022
DOI: 10.3390/buildings12040419
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Dredged Sediments in Manufacturing Compressed Earth Blocks Stabilized by Alkali-Activated Fly Ash Binder

Abstract: The valorization of dredged sediments is a promising solution to reduce the strain on natural resources, which is in line with sustainable development goals. This study aims to evaluate the potential valorization of dredged sediment in manufacturing compressed earth blocks (CEBs). The CEBs were stabilized by a combination of fly ash (FA) with sodium hydroxide (NaOH). The stabilization was achieved by partial substitution of sediment for fly ash with six different percentages 10, 20, 30, 40, and 50% by weight. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…CDWs are increasingly recognized as valuable resources for producing cementitious materials and road paving [1]. Simultaneously, the construction sector shows a growing interest in developing compressed earth bricks [2][3][4]. Typically, these bricks are stabilized with mineral binders such as Portland cement to enhance their properties and performance [2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDWs are increasingly recognized as valuable resources for producing cementitious materials and road paving [1]. Simultaneously, the construction sector shows a growing interest in developing compressed earth bricks [2][3][4]. Typically, these bricks are stabilized with mineral binders such as Portland cement to enhance their properties and performance [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the construction sector shows a growing interest in developing compressed earth bricks [2][3][4]. Typically, these bricks are stabilized with mineral binders such as Portland cement to enhance their properties and performance [2,4]. In line with environmentally conscious efforts, this study aims to investigate the feasibility of creating an eco-friendly brick.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the research carried out by [ 1 ], the sediments were incorporated into the brick-manufacturing process instead of quartz sand. In addition, it has been shown that a 50% replacement of natural brick-making clay by sediments allows for reaching the compressive strength required for the American Society for Testing and Materials (ASTM) standards [ 2 , 3 ]. The feasibility of using dredged sediments as a partial replacement for cement in mortars was assessed by several authors [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Placing dredged sediments in landfills, which is expensive, is only practiced when there are no other solutions (Maherzi et al, 2018). However, dredged sediments can be considered as alternative resources rather than waste (Brahim et al, 2022). With the current limited availability of high-quality aggregates, using dredged sediments as a construction material can optimize their future management (Maherzi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The suitability of using dredged sediments in lightweight aggregate production has been reported in the literature due to their perpetual availability, homogeneity, and mineralogical and chemical composition (Liu et al, 2018;Ennahal et al, 2021). Dredged sediments have also been used in brick production (Brahim et al, 2022;Slimanou et al, 2019). The replacement of 15% of quartz sand with sediments has resulted in a 63% increase in compressive strength and a 10% decrease in porosity (Ouédraogo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%